Augmentation index (AI) in a dose–response relationship with smoking habits in males: The Tanushimaru study. Issue 51 (December 2016) - Tsuru, Tomoko; Adachi, Hisashi; Enomoto, Mika; Fukami, Ako; Kumagai, Eita; Nakamura, Sachiko; Nohara, Yume; Kono, Shoko; Nakao, Erika; Sakaue, Akiko; Morikawa, Nagisa; Fukumoto, Yoshihiro
Abstract : Abstract: We investigated the relationship between augmentation index (AI) and smoking habits in community-dwelling Japanese. This cross-sectional study enrolled 1926 subjects (769 males and 1157 females) aged 40 to 95 years who underwent a health check-up in a Japanese cohort of the Seven Countries Study, in Tanushimaru, a typical farming town in Kyushu Island in 2009. The subjects' medical history, alcohol intake, smoking habit, and current medications for hypertension, dyslipidemia, and diabetes were ascertained by questionnaire. Radial arterial pressure wave analysis was used to obtain AI. We analyzed the data stratified by gender. Age-adjusted means of AI in males showed a clear dose–response relationship in 4 categories of smoking habits ( P = 0.010). There was no significant relationship between AI and smoking habits in females ( P = 0.127). The significant dose–response relationship ( P = 0.036) in males between AI and 4 categories of smoking habits still remained even after adjustment for age, body mass index, systolic blood pressure, estimated glomerular filtration rate, glucose, hypertensive medication, and alcohol intake. The present study demonstrated that AI values were significantly associated with smoking habits in a dose-dependent manner in Japanese males.